Pengaruh Media Digital Flipbook Terhadap Peningkatan Hasil Belajar Bahasa Indonesia Siswa di Sekolah Dasar - Wulan Dwi Septiani; Tri Linggo Wati (IJPSE Indonesian Journal of Primary Science Education, 2026)
This study aims to analyze the effect of using digital flipbook media on improving the Indonesia Language learning outcomes of third-grade students at SDN Sudimoro in the 2025/2026 academic year. This study used a quantitative approach with a one group pretest- posttest pre experimental design. The research subjects were given a pretest before the treatment and a posttest after the application of the digital flipbook media. Data collection was conducted through learning outcome test, then analyzed using a paired t-test. The analysis results showed that the average pretest score of 51 increased to 88.33 on the posttest. The paired t-test value obtained was t=12.322 with Sig. (2-tailed) = 0.000 ( < 0,05), indicating a significant difference between the scores before and after the treatment. Based on these findings, it can be concluded that the use of flipbook digital media has a significant effect on improving Indonesia Language learning outcomes in SPOK material for third- grade student. In short, this this media is effective in helping student understand, apply, and analyze sentence structure more systematically.